DEVELOPMENT OF BASIC KUMITE KARATE TRAINING ANDROID BASED ON THE WHITE BELT BLUE KARATE-DO KKI MEDAN IN 2021 - Sinaga, Johanes Nata Nael; Damanik, Saipul Ambri (Universitas Negeri Medan, 2023)
This study aims to produce an android-based application called